(3GdSjGSI GdLfGFjI dehGLgI GdGYJOGA Ydi GdHjFI ai GdbGfhf GdchjJi (B: s (3OQGSI ebGQfI (B/ s - (3NGdO MSjf eMeO HQGc MVjQi GdOhSQis; (3CMeO YhV HdGd s; (3YeQ eMeO eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3Ef dcd YUQ ef GdYUhQ bVjI JWQM faSgG h JTZd Ybhd GdeacQjf(B: (3h dG Tc Cf bVjI ReffG gPG gi bVjI GdJdhK GdHjFj h GdeTGcd GdJi JeS GdHjFI(B: (3h GdJi JgOO GdEfSGf ai MjGJg(B: (3MjK JYJHQ GdHjFI GdhSW GdMjhi GdPi JYjT ajg GdeNdhbGJ ef EfSGf hMjhGf h fHGJ(B: (3h bO Yed GdHTQ Ydi GdGYJOGA Ydi GdehGQO GdWHjYjI dgPg GdHjFI hJcjja hJWhjY GdHjFI dQZHGJge MJi JLGhRhG GdMOhO(B: (3h dG jhLO GNWQ eeG jMOK Gdjhe ef EJdGa ddHjFI Edi GdMO GdPi LYd ef GdUYH EUdGM eG Je EaSGOg(B: (3h eG eTcdI GdGMJHGS GdMQGQi EdG eKGd Mj dPdc (B: (3h gh eG jgOO HCf JUHM GdMjGI bGSjI Ydi chcHfG (B: (3aCUHMJ gPg GdXGgQI JTcd eTcdI EfSGfjI h NGUI HYO GdJbOe GdJcfhdhLj GdgGFd GdPi hUd dg GdEfSGf h GdKhQI GdUfGYjI GdJj SGgeJ aj Qbj GdEfSGf ef LgI h ef LgI CNQi GfYcSJ HSdH Ydi HjFJg(B: (3ceG Ef GdeSDhdjI GdLRGFjI HGYJHGQgG eSDhdjI bGfhfjI jbUO HgG KHhJ GdLQjeI Edi GdTNU GdPi CQJcH aYdG ZjQ eTQhY jUHM HebJVGg eSJMbG ddYbhHI GdJi bQQgG GdbGfhfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2017s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B330-353s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJdhK GdHjFis; (3GdJTQjYGJ GdHjFjIs; (3LQGFe GdJYQjV ddNWQ GdYGes; (3LQGFe GdHjFIs; (3LQjeI GdGYJOGA Ydi GdHjFIs; (3eSFhdjI eOjQ GdefTGI GdYGeI Yf LQGFe GdHjFIs; (3GdJTQjY GdchjJis; (3GdGNJUGU HLQGFe GdHjFIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs